2013
DOI: 10.1097/iop.0b013e318295fa09
|View full text |Cite
|
Sign up to set email alerts
|

Supratrochlear and Supraorbital Nerves

Abstract: The data presented in the current study are in agreement with previous anatomical studies. Both ST and SO nerves can be used as sensory nerve donors in the head and neck area for numerous expanding applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…In the present study, the distance of the SON to the midline was found as 2.60 ± 0.4 cm, and this is compatible with previous studies, which reported a range of 1.93 ± 0.21 to 3.2 cm (4,10,11,20,27). There was no difference between sexes, sides, or cadaver groups.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the distance of the SON to the midline was found as 2.60 ± 0.4 cm, and this is compatible with previous studies, which reported a range of 1.93 ± 0.21 to 3.2 cm (4,10,11,20,27). There was no difference between sexes, sides, or cadaver groups.…”
Section: Discussionsupporting
confidence: 92%
“…The supraorbital nerve usually exits via the supraorbital foramen in the medial orbital rim and then branches into medial and lateral branches. The medial branch crosses and runs superficially over frontal muscle to supply the forehead skin and anterior scalp as far as the vertex, whereas the lateral branch lateralizes, traveling on periosteum 1 cm medial and parallel to the temporal crest and enters the galea in the cranial portion of the forehead, providing sensitivity to the parietal region [101112]. When an anesthetic solution is injected, it is considered to have been injected into the subcutaneous space, but in most cases, an anesthetic solution is delivered after the inserted spinal needle touches bone, and thus, the anesthetic solution is injected into the periosteal space rather than the subcutaneous space, which causes a bleb-like cyst (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Some anatomical studies have documented the exit point of the STN from the orbit, the relationship between the SON and STN, and the point at which these nerves enter the CSM, with a focus on clinical applications [ 12 , 21 , 23 , 24 ]. The present study revealed the branching patterns of the STN in the supraorbital area.…”
Section: Discussionmentioning
confidence: 99%
“…However, while it is quite easy to find surface landmarks to enable SON block, it is quite difficult to find appropriate surface landmarks to enable anesthetization of the STN, despite the numerous studies describing the morphology of that nerve. This has resulted in numerous unnecessary injections to induce STN anesthesia in the forehead skin, and when it is achieved; this anesthesia is less effective compared with SON block [ 12 , 22 , 23 , 24 ]. Only a few of the studies that have investigated the STN morphology have described its patterns of emergence from the orbit and its course through the CSM.…”
Section: Introductionmentioning
confidence: 99%